Re-designing irrigated intensive cereal systems through bundling precision agronomic innovations for transitioning towards agricultural sustainability in North-West India - Jat, Hanuman Sahay; Sharma, Parbodh Chander; Datta, Ashim; Choudhary, Madhu; Kakraliya, S.; Singh, Yadvinder; Sidhu, Harminder S.; Gerard, Bruno G.; Jat, Mangi Lal (Springer, 2019)
A study was conducted to design productive, profitable, irrigation water¸ nitrogen and energy use efficient intensive cereal systems (rice-wheat; RW and maize-wheat; MW) in North-West India. Bundling of conservation agriculture (CA) with sub-surface drip irrigation termed as CA+ were compared with CA alone and conventional tillage based and flood irrigated RW rotation (farmer’s practice; ScI). In contrast to conventional till RW rotation which consumed 1889 mm ha−1 irrigation water (2-yr mean), CA+ system saved 58.4 and 95.5% irrigation water in RW and MW rotations, respectively. CA+ practices saved 45.8 and 22.7% of irrigation water in rice and maize, respectively compared to CA with flood irrigation. On a system basis, CA+ practices saved 46.7 and 44.7% irrigation water under RW (ScV) and MW (ScVI) systems compared to their respective CA-based systems with flood irrigation (ScIII and ScIV). CA+ in RW system recorded 11.2% higher crop productivity and improved irrigation water productivity by 145% and profitability by 29.2% compared to farmers’ practice. Substitution of rice with maize (MW system; ScVI) recorded 19.7% higher productivity, saved 84.5% of irrigation water and increased net returns by 48.9% compared to farmer’s practice. CA+ RW and MW system improved energy productivity by 75 and 169% and partial factor productivity of N by 44.6 and 49.6%, respectively compared to ScI. The sub-surface drip irrigation system saved the fertilizer N by 20% under CA systems. CA+ in RW and MW systems recorded ~13 and 5% (2-yr mean) higher profitability with 80% subsidy on installing subsurface drip irrigation system and similar profitability without subsidy scenario compared with their respective flood irrigated CA-based systems.